2019
DOI: 10.1002/slct.201903171
|View full text |Cite
|
Sign up to set email alerts
|

N‐Ethyl Carbazole Derived D‐π‐A‐π‐D Based Fluorophores: Consolidated Spectroscopic, Viscosity and DFT Studies

Abstract: This article reports design and synthesis of three new fluorophores (5 a‐c) with the donor‐π‐acceptor‐π‐donor motif, where dicyano vinylene group is the central acceptor, N‐ethyl carbazole group is a fixed donor and varying the N‐substituted secondary donors so as to study their photophysical behavior. Based on the systematic photophysical and theoretical reconnaissances, the fluorophores structure‐property relationships are defined. Their spectral and photophysical behaviors are affected by the solvent polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…On [24] by the same level of this work in 17.35-24.24 Â 10 À24 esu in the CHCl 3 . Also, the β tensor for the urea molecule, which is a prototype compound using for the comparison purpose, was reported [31] in 0.6230 Â 10 À30 esu.…”
Section: Nlo (Non-linear Optic) Analysismentioning
confidence: 53%
See 1 more Smart Citation
“…On [24] by the same level of this work in 17.35-24.24 Â 10 À24 esu in the CHCl 3 . Also, the β tensor for the urea molecule, which is a prototype compound using for the comparison purpose, was reported [31] in 0.6230 Â 10 À30 esu.…”
Section: Nlo (Non-linear Optic) Analysismentioning
confidence: 53%
“…Also, the chemical shifts for the C30, C37, and C41 have given the signals in 57.9, 52.6, and 53.2 ppm, respectively, and calculated in 68.0, 58.0, and 58.5 ppm (in CHCl 3 ). Recently, the aromatic 13 C chemical shifts for the carbazole substituted malononitrile derivatives were observed in 108.7-141.4 ppm, 108.8-151.0 ppm, and 108.6-150.4 ppm [24] and the unsaturated ring 13 C shifts for one of the studied compounds 21.0-60.4 ppm. Also, 13 C shifts for the aromatic and unsaturated rings of the hyperoside compound were reported [25] in 156.2-103.9 ppm and 71.2-60.1 ppm, respectively.…”
Section: Nmr Analysismentioning
confidence: 98%
“…To introduce D–A functionalities onto the carbazole scaffolds, numerous synthetic approaches have been reported in the literature, which mainly include organometal-catalyzed reactions. Sekar et al have reported carbazole-derived D−π–A−π–D-based fluorophores via condensation of 2-[1-(9-ethyl-9 H -carbazol-3-yl)­ethylidene]­malononitrile with different aldehydes . Zhao et al have synthesized carbazoles containing D–A cyclopropanes by regioselective N–H/C–H functionalization of carbazole in the presence of TfOH or Sc­(OTf) 3 , but these procedures require either expensive metal catalysts or harsh reaction conditions.…”
Section: Resultsmentioning
confidence: 99%